ANALISIS HISTORICAL TRADITIONAL FISHING RIGHT PADA ZONA EKONOMI EKSKLUSIF (ZEE) INDONESIA - Prakasa, Satria Unggul Wicaksana; Purwo, Al-Qodar (Legality : Jurnal Ilmiah Hukum, 2019)
Indonesian people are shocked by the case of the Chinese Fisheries (KM) with the name KM Kway Fey 10078 which is categorized as a Foreign Fish Boat (KIA) fishing around the Natuna Islands waters which are the territorial waters of the Indonesian EEZ. The concept of historical traditional fishing ground towards waters in the Natuna sea region which in fact is still an Indonesian EEZ area needs to be further analyzed. The formulation of the problem in legal research are: (1). Theoretical and regulatory regarding Historical Traditonal Fishing Ground based on UNCLOS 1982. (2). The provisions of IUU Fishing are based on UNCLOS 1982 and Indonesian legislation is applied in the case of Historical Traditonal Fishing Ground which catches fish in Indonesian (EEZ) waters. Legal research methods are used with statute approaches and conceptual approaches. The results of this research are (1). If without a bilateral agreement, it is in accordance with the UNCLOS 1982 Historical Traditions of Fishing Ground is categorized as one of the IUU Fishing and violations of jurisdiction and territorial integrity of Indonesia, where Indonesian legal authorities have the right to take action on every fisherman who claims to have traditional fishing rights in accordance with Indonesian legal mechanisms. (2). Needs support from countries to implement policies, programs, and practices from these countries to make this rule implementable, so that there is an impact of remedy for countries that are considered to do IUU Fishing under the pretext of using historical traditional fishing right, then fish commodities arrested was prohibited from being traded on the international market, because the commodity was captured from a process of violation of international marine law and violation of jurisdiction and sovereignty of the State.